A (in)definitude no sintagma nominal em libras : uma investigação na interface sintaxe-semântica - Almeida-Silva, Anderson, 1987- (2019)
Orientadores: Ruth Elisabeth Vasconcellos Lopes, Josep Francisco Quer Villanueva